Organized crime and American power : a history / Michael Woodiwiss. - Woodiwiss, Michael (University of Toronto Press, 2001)
This wide-ranging history argues that organized criminal activity has never been a serious threat to established economic and political power structures in the US but more often a fluid, variable phenomenon that has complemented those structures.